Factors associated with the maintenance of exclusive breastfeeding in the late postpartum - Vanessa Aparecida Gasparin; Juliana Karine Rodrigues Strada; Bruna Alibio Moraes; Thaís Betti; Érica de Brito Pitilin; Lilian Cordova do Espírito Santo (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: To identify the factors associated with the maintenance of exclusive breastfeeding and to verify the justification for the introduction of other liquids in the late postpartum of mothers and children attended by a breastfeeding consultant. Method: A non-comparative prospective cohort, conducted with 150 mothers and children. Data was collected at rooming-in 15 and 30 days after birth and analyzed by univariate analysis and multivariate regression. Results: The reasons for introducing water, tea, and breast milk substitutes were the following: thirst, abdominal cramps, and infant crying, respectively. Vaginal delivery, not using a pacifier or bottle and seeking professional help after discharge were associated with the exclusivity of late postpartum breastfeeding. Conclusion: The introduction of a professional breastfeeding consultant is of significant importance in the rise of exclusive breastfeeding rates.